"Click like if you like it": the effect of directional posts on social network sites. Issue 5 (11th September 2017) - López, Manuela; Sicilia, Maria; Verlegh, Peeter W.J.
Abstract : Purpose: Social network sites (SNSs) are an important part of consumers' everyday lives, and have been recognized as a useful marketing channel. However, little is known about how brands should communicate in order to be more effective and maximize the diffusion of electronic word of mouth (eWOM) in these platforms. The purpose of this paper is to explore the effect of directional posts on consumers depending on previous diffusion of the post and consumers' connectivity. Design/methodology/approach: A between-subjects experimental design was used. The sample consisted of 369 individuals. Findings: The results show that directional posts only enhance the intention to spread eWOM and the attitude toward the product when the brand post was highly diffused. This effect is stronger among highly connected consumers (hubs) than among less well-connected individuals. Originality/value: To the best of the authors̓ knowledge, this is one of the first studies to analyze the persuasiveness of marketers' explicit encouragements to "like" brand posts, a tactic known as directional posts. The study investigates whether and how consumer responses to directional posts are influenced by responses from others and by the number of connections that consumers have within the SNSs.